2019
DOI: 10.1111/ina.12558
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of indoor surface finishes on bacterial viability

Abstract: Microbes in indoor environments are constantly being exposed to antimicrobial surface finishes. Many are rendered non‐viable after spending extended periods of time under low‐moisture, low‐nutrient surface conditions, regardless of whether those surfaces have been amended with antimicrobial chemicals. However, some microorganisms remain viable even after prolonged exposure to these hostile conditions. Work with specific model pathogens makes it difficult to draw general conclusions about how chemical and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…On indoor surfaces that lack abundant moisture and nutrient availability, most microorganisms that arrive from other environments (such as from human occupants) are generally considered unlikely to survive, and those viable microbes that do survive are generally considered to be inactive or dormant until transferred to other host locations or until they experience an influx of moisture and nutrients that help them proliferate [4••, [50][51][52]. Surveys of fungal communities in indoor environments, conducted using high-throughput molecular sequencing, have shown that they tend to be driven primarily by transport from the local outdoor environment [31].…”
Section: Microbial Community Ecology On Fomite Surfacesmentioning
confidence: 99%
“…On indoor surfaces that lack abundant moisture and nutrient availability, most microorganisms that arrive from other environments (such as from human occupants) are generally considered unlikely to survive, and those viable microbes that do survive are generally considered to be inactive or dormant until transferred to other host locations or until they experience an influx of moisture and nutrients that help them proliferate [4••, [50][51][52]. Surveys of fungal communities in indoor environments, conducted using high-throughput molecular sequencing, have shown that they tend to be driven primarily by transport from the local outdoor environment [31].…”
Section: Microbial Community Ecology On Fomite Surfacesmentioning
confidence: 99%
“…It is one of relatively few clades near-universally prevalent on human skin as a commensal, and as a result is widely distributed in the built environment; it can also drive significant opportunistic infection [68]. In fact, the clade represents a serious human health risk via antimicrobial resistance [59] in the built environment, often associated with high-touch surfaces where it can remain viable for days [69][70][71]. Finally, because one of our metagenomes contained a high relative abundance of Staphylococcus-associated reads, we were confident that we would find Staphylococcus within the culture isolates generated from that sample.…”
Section: Discussionmentioning
confidence: 99%
“…DNA quality was measured with a Synergy HTX Multi-Mode Reader (BioTek, Winooski, VT, USA) and was considered acceptable for downstream analysis if the 260/280 ratio was between 1.7 and 2.1. DNA concentrations were quantified using the Quant-iT™ dsDNA Assay Kit (ThermoFisher Scientific, Waltham, MA, USA) [ 44 ]. Seven of the 34 samples were originally found to have relatively low yields of DNA that were below requirements for the library prep (0.2 ng uL −1 ); these samples were re-processed with the same steps above using 5 mL of toothbrush head supernatant.…”
Section: Methodsmentioning
confidence: 99%